Respuesta :

m=s(q_2-q_1)

m/s=q_2-q_1

q_2=m/s  +  q_1

Given :

  • [tex] \tt m = s(q_2 - q_1) [/tex]

To Find :

  • [tex] \tt q_2 = ?[/tex]

Solution :

[tex] \tt \dashrightarrow m = s(q_2 - q_1) [/tex]

[tex] \tt \dashrightarrow \dfrac{m}{s} = q_2 - q_1[/tex]

[tex] \tt \dashrightarrow \dfrac{m}{s} + q_1= q_2[/tex]

[tex] \tt \dashrightarrow q_2 = \dfrac{m}{s} + q_1[/tex]

[tex] \large \underline{\boxed{\bf{q_2 = \dfrac{m}{s} + q_1}}}[/tex]

Hence, value of [tex] \tt q_2 = \dfrac{m}{s} + q_1[/tex]